2017
DOI: 10.1002/trtr.1556
|View full text |Cite
|
Sign up to set email alerts
|

Children Creating Multimodal Stories About a Familiar Environment

Abstract: Storytelling is a practice that enables children to apply their literacy skills. This article shares a collaborative literacy strategy devised to enable children to create multimodal stories about their familiar school environment. The strategy uses resources, including the children's own drawings, images from Google Maps, and the Puppet Pals Director's Pass app, to leverage children's experiences in their school and community contexts for a meaningful and authentic literacy learning opportunity. The children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 12 publications
1
19
0
3
Order By: Relevance
“…The creation of a map text enables children to articulate the extent to which they themselves identify spatial location and context as contributing to the meaning conveyed by an image-based text. Kervin and Mantei (2017) engaged young children in the creation of multimodal map texts which brought together storytelling and their understanding of the known environment of the school. A task was designed for one Australian primary school class, to create their own map of the school using paper and coloured pens, alongside a 2D puppet figure.…”
Section: Mapping the Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The creation of a map text enables children to articulate the extent to which they themselves identify spatial location and context as contributing to the meaning conveyed by an image-based text. Kervin and Mantei (2017) engaged young children in the creation of multimodal map texts which brought together storytelling and their understanding of the known environment of the school. A task was designed for one Australian primary school class, to create their own map of the school using paper and coloured pens, alongside a 2D puppet figure.…”
Section: Mapping the Environmentmentioning
confidence: 99%
“…A further key observation from the study may be found in children's use of their 2D puppet character. Kervin and Mantei (2017) suggest that the movement of the puppet characters around the map 'provided concrete spatial resources to prompt children's recall of familiar events and practices' (723). When considering this activity in light of Hackett's (2014) observations of the embodied practices of younger children, the possibility arises that it is these physical engagements which the children in the study are representing and drawing upon to support and convey their own meaning.…”
Section: Mapping the Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Il est admis qu'à notre époque le numérique, le visuel et le virtuel prennent une place de plus en plus grande dans la vie de tous les jours (Matusiak, 2011). La technologie numérique permet la création de tâches multimodes : linguistique, audio ou sonore, visuel, spatial et gestuel (Kervin et Mantei, 2017). Dans ce contexte, la littératie est une activité sociale qui se vit quotidiennement dans le temps et l'espace d'une manière continue et transdisciplinaire (Casey, 2013).…”
Section: Introductionunclassified
“…Dans ce sens, si les pratiques de littératie chez les élèves sont socialement situées, il convient de leur offrir des occasions d'apprentissage authentiques et stimulantes (Kervin et Mantei, 2017). Ce contexte, signifiant pour l'apprentissage de la lecture et de l'écriture, est particulièrement important pour les élèves francophones en milieu minoritaire canadien.…”
unclassified